Factors predicting nutritional knowledge, illness perceptions, and dietary adherence among hypertensive middle-aged women: Application of transtheoretical model - Bahram Mohebbi; Banafsheh Tafaghodi; Roya Sadeghi; Azar Tol; Mir Saeed Yekanenejad (Journal of Education and Health Promotion, 2021)
BACKGROUND: Healthy dietary adherence might be one of the effective and modifiable factors for hypertension (HTN) control; therefor, empowering patients for self-care management including healthy food patterns play a key role in guiding their care, in partnership with health care providers. This study aimed to identify the factors predicting nutritional knowledge, illness perceptions, and adherence to a diet based on transtheoretical model (TTM) among hypertensive middle-aged women. MATERIALS AND METHODS: A cross-sectional survey was conducted on 164 patients with HTN attending west health centers of Tehran, Iran, in 2020. Simple random sampling was used. Sociodemographic characteristics of the respondents were collected, a valid and reliable measure on nutritional knowledge, illness perceptions, and adherence to diet, and a researcher-made measure based on TTM constructs through in-person interview was applied. Descriptive statistics and general linear model were utilized for data analysis using SPSS version 25. The significance level was considered less than 0.05. RESULTS: Mean and standard deviation of participants was 50.82 ± 8.77 years. Multivariate regression analysis indicated that family income (P < 0.001) and body mass index (P < 0.001) predicted nutritional knowledge and adherence to diet, respectively. Decisional balance and self-efficacy constructs predicted nutrition knowledge and illness perceptions (P < 0.001). In adherence to diet, overcoming the temptation construct was indicated as the only predictor (P < 0.001). CONCLUSION: Study findings highlighted the necessity of tailoring and implementing interventions based on TTM using appropriate strategies to promote quality of HTN management approach in nutritional knowledge, illness perceptions, and dietary adherence.